Recursos didácticos y su incidencia en el desempeño académico de los estudiantes de electricidad del primer año del colegio fiscal de bachillerato “Simón Bolívar” cantón Guayaquil, provincia Guayas - Blacio Litardo, David Lorenzo (2018)
This research project is supported by studies conducted in the international, national and local context on didactic resources that are those materials that favor the teaching-learning process and facilitate the interpretation of content that the teacher has to teach. The main objective was to determine the incidence of didactic resources in the academic performance of the first-year students of electricity of the secondary school "Simón Bolívar", with the purpose of observing the effects of the problem in the classroom. The contents are based on the theory of Significant Learning by David Ausubel. In the research study the random sampling technique was used, represented by 16 teachers and 40 students. The results indicate 87.5% (14) and 40% of the students corroborate that the institution lacks didactic resources, 15% sometimes and 10% do not use didactic material in the classroom. 62.5% of teachers do not involve students in the preparation of resources, just as Tics do not apply in the educational process. In reference to the methodologies, 50% are not adequate in the development of competencies. Finally, measuring the implementation of a 100% technical guide will have a positive impact on academic performance and educational processes